Erythrocyte-neutrophil interactions: formation of leukotriene B4 by transcellular biosynthesis. - McGee, J E (1986)
Studies on the mechanism of leukotriene B4 biosynthesis in suspensions composed of neutrophils plus erythrocytes indicate that human erythrocytes convert neutrophil-derived leukotriene A4 into leukotriene B4. Leukotriene B4 formation by neutrophils in the presence of erythrocytes exceeded that from corresponding suspensions of neutrophils alone. The increase was proportional to the erythrocyte content of the suspension. The erythrocyte-dependent increase in leukotriene B4 biosynthesis did not equal the arithmetic sum of calcium ionophore-dependent biosynthesis by neutrophils plus calcium ionophore-dependent biosynthesis by erythrocytes, since erythrocytes produced no leukotriene B4 upon incubation with ionophore A23187. Erythrocytes did not stimulate 5-lipoxygenase activity within neutrophils, since the erythrocyte effect was confined to enzymatic hydration: leukotriene B4 increased coincident with decreased formation of 5,12-dihydroxyicosatetraenoic acids derived from nonenzymatic hydration. Biosynthesis of leukotriene B4 within the erythrocyte, from neutrophil-derived leukotriene A4, was established by comparing the effect of normal erythrocytes with erythrocytes containing a leukotriene A4 hydrolase that was inactivated by the substrate. In the latter case, leukotriene B4 formation increased by only 30-40%; in the former case, it increased by 100-200%. Transcellular biosynthesis of leukotriene B4 from erythrocyte-neutrophil interactions explains the paradoxical presence of leukotriene A4 hydrolase within erythrocytes, a cell incapable of synthesizing leukotriene A4; affords a mechanism to overcome rate limitations or "suicide inactivation" of leukotriene A4 hydrolase in neutrophils; exploits a cryptic capacity within erythrocytes, provisionally dormant cells in terms of icosanoid biosynthesis; indicates that the biosynthetic capacity of cell combinations is not necessarily equivalent to the sum of their separate capacities.